2008
DOI: 10.48044/jauf.2008.007
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Residents Toward Street Trees on Four Streets in Toledo, Ohio, U.S. Before Removal of Ash Trees (Fraxinus spp.) from Emerald Ash Borer (Agrilus planipennis)

Abstract: Toledo, Ohio, U.S. residents on four streets in an area with mature street trees, including ash, scheduled for removal as a result of attack by emerald ash borer were surveyed to determine their attitudes toward their street trees. Toledo is in the process of removing some 5,000 trees. Large trees with a variety of summer and fall foliar characteristics were highly valued suggesting that residents would be satisfied with a mix of species rather than planting each street to a single species. The fact that their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…While the observed changes of perceived importance were small, this confirms findings from other studies that have observed changes in perceived preference for urban places with or without trees (Arnberger et al, 2017), and points towards the contribution that trees make to the importance of urban nature sites: having more trees makes these sites more important to people. Moreover, the observed changes in tree planting attitudes were both significant and meaningful, reflecting results from other studies that report changes in tree attitudes after urban tree loss or removal (Heimlich et al, 2008; Hunter, 2011). However, while such changes can be immediate and generally positive (i.e.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…While the observed changes of perceived importance were small, this confirms findings from other studies that have observed changes in perceived preference for urban places with or without trees (Arnberger et al, 2017), and points towards the contribution that trees make to the importance of urban nature sites: having more trees makes these sites more important to people. Moreover, the observed changes in tree planting attitudes were both significant and meaningful, reflecting results from other studies that report changes in tree attitudes after urban tree loss or removal (Heimlich et al, 2008; Hunter, 2011). However, while such changes can be immediate and generally positive (i.e.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, some ecological changes may not be as evident to humans or readily translate into human perception responses. As shown previously, changes in biodiversity may influence cognitive, affective and behavioural human responses (Fisher et al, 2021; Fuller et al, 2007; Lindemann‐Matthies et al, 2010; Schebella et al, 2019; Shwartz et al, 2014; Straka et al, 2016), and cognitive changes in perception may influence how people experience treed places, and, consequently, the benefits people derive from these spaces (Arnberger et al, 2017; Avolio et al, 2015; Heimlich et al, 2008; Hunter, 2011; Oh et al, 2021; Schebella et al, 2017, 2019; Veitch et al, 2014). However, as demonstrated in this study, some people may not cognitively respond to changes in tree abundance or biodiversity structure and processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Street trees → damage sidewalks (Ely, 2009;Heimlich et al, 2008;Kirkpatrick et al, 2012;McPherson and Peper, 1996) → reduce walkability → reduce physical activity → increase negative affect Prevent capacity building…”
Section: Andersonmentioning
confidence: 99%